Pengembangan Bahan Ajar Berbasis Multiple Intelligences untuk Meningkatkan Hasil Belalajar Siswa Sekolah Dasar - Kardiana Metha Rozhana; Moh. Farid Anwar (Universitas Kanjuruhan Malang, 2022)
Difficulties in teaching during the COVID-19 pandemic are felt by students, teachers, and parents. Cognitive abilities are also less honed because during Learning from Home students' work is done by parents. The purpose of developing these teaching materials is to help students improve learning outcomes and improve cognitive abilities. The method used in this study is a 4-D model and modified into 3 stages, namely defining, designing, and developing. The results of the validation test and field test obtained a percentage of 90.6% and it is said to be very valid so that it is suitable for use in learning. This product can also be implemented in other schools in the fourth grade of elementary school.